Analisis Kualitas Butir Soal Konsep Sistem Gerak Manusia Kelas VI Sekolah Dasar Berdasarkan Validitas, Reliabilitas, Tingkat Kesukaran dan Daya Beda - Ika Isna Umiyati; Fina Fakhriyah; Sumaji Sumaji (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
The quality of assessment instruments plays an important role in determining the accuracy of measuring student learning outcomes in science learning in elementary schools. A good test instrument must meet certain criteria, such as validity, reliability, difficulty level, and discrimination power. This study aims to analyze the quality of daily science test items in grade VIc elementary schools based on these four criteria. The study used a quantitative. The subjects were 19 sixth-grade students, while the instrument analyzed consisted of 25 multiple-choice questions. Data processing and analysis were carried out using Microsoft Excel to calculate item validity through item correlation with total score, test reliability using internal consistency, difficulty level index, and discrimination index. The analysis results showed that 17 questions (68%) were declared valid, while 8 questions (32%) were invalid and needed to be improved. The results of the reliability test indicated that the test instrument had good reliability and was suitable for use as a measuring tool for student learning outcomes. Judging from the level of difficulty, 20 questions (80%) were moderate and 5 questions (20%) were easy, indicating a relatively balanced level of difficulty. Based on the discrimination power, 16 questions (66%) had very good discrimination power, 4 questions (16%) were good, 4 questions (16%) were sufficient, and 1 question (4%) was poor. Based on these findings, it can be concluded that the quality of the sixth grade science daily test questions is classified as good and the test instrument is suitable for use, but improvements are still needed on invalid questions and those with low discrimination power so that the quality of the assessment is more optimal. This study emphasizes the importance of teachers' abilities in compiling and analyzing test items to ensure that the assessment of science learning is objective, valid, and reliable.